PETROGENESIS AND TECTONIC SETTING OF VOLCANIC ROCKS FROM THE SUBPELAGONIAN OPHIOLITIC MÉLANGE IN THE AGORIANI AREA (OTHRYS, GREECE) - Photiades, Adonis; Saccani, Emilio; Tassinari, Renzo (Ofioliti, 2003)
In the northwestern end of the Othrys Massif, the lowermost unit of the Othrys ophiolitic complex is represented by the Agoriani Mélange, which is a typical tectono-sedimentary mélange developed at a convergent margin, and comprises ophiolite-derived turbidites and debris flow deposits including, in turn, various oceanic-crust lithotypes. The volcanic rocks recorded in the Agoriani Mélange are represented by chemically distinct rock groups.Group 1 is characterized by MOR-type basalt and basaltic andesite, showing high-Ti geochemical affinity, and flat HFSE patterns, as well as mild LREE depletion (LaN/SmN = 0.48-0.69) coupled with an overall enrichment for HREE. The chemistry of these rocks is compatible with about 20% partial melting of an undepleted MORB-type mantle source.Group 2 is represented by basalts whose geochemical characteristics are intermediate between typical low-Ti island arc tholeiites and pure high-Ti MORBs. Nonetheless, the strong depletion of Th, Nb, and LREE (LaN/SmN = 0.02-0.20) and the mild depletion of HFSE are consistent with the compositions of magmas generated in supra-subduction zone settings from partial melting of refractory mantle sources. In particular, these rocks are compatible with about 10% partial melting from a mantle source that had experienced about 20% previous MORB melt extraction.Group 3 includes basaltic andesites and andesites showing chemical features typical of very low-Ti (boninitic) rocks: that is, strong depletion of HFSE and depleted, U-shaped REE patterns. The chemical features displayed by Group 3 rocks are compatible with 10 - 20% partial melting of mantle sources (enriched in LILE and LREE by subduction-derived fluids), representing the residua after Group 2 primary melt extraction.One sample is represented by alkaline basalt, as testified by the incompatible elemental ratios, as well as the marked LILE and LREE enrichments. The overall chemical features are comparable to those of typical ocean island basalts (OIBs), and are consistent with ca. 5% partial melting of a theoretical plume source.According to the regional reconstruction of the Neo-Tethys, the volcanic lithologies included in the Agoriani Mélange are consistent with the magmatic activities that occurred in the Pindos oceanic basin from the Permian-Triassic rifting stage and Triassic-Jurassic oceanization (including seamounts) to the Middle-Late Jurassic intra-oceanic subduction.Group 2 basalts, in particular, correspond to basalts with peculiar chemistry sporadically found in both north and south Albania. The genesis and tectono magmatic significance of these basalts is discussed in this paper on the bases of three possible models.